Effect of Eye Height on Estimated Slopes of Hills. (July 2015) - Bridgeman, Bruce; Cooke, Ian
Several studies have shown that slopes of hills are greatly overestimated. We have recently demonstrated that the overestimates increase logarithmically as the end point of the domain to be estimated is increased. A theoretical analysis showed that a critical parameter is the angle between the observer's line of sight and the slope of the hill, when the observer fixates the far point of the required domain. The theory predicts that increasing the observers' eye height will increase this angle, thus reducing the overestimates. Here, we test that theory by having observers stand on a box to increase their eye height. Slope estimates for various ranges again followed a logarithmic function, with lower estimates at nearer distances compared with other observers standing directly on the surface of the hill. At larger distances, slope estimates with and without increased eye height converged.